Targeting breast cancer using pirarubicin-loaded vasoactive intestinal peptide grafted sterically stabilized micelles - Eskandari, Zahra; Bahadori, Fatemeh; Yapaoz, Melda Altikatoglu; Yenigun, Vildan Betul; Celikten, Mert; Kocyigit, Abdurrahim; Onyuksel, Hayat (ELSEVIER, 2021)
In this study the chemotherapeutic agent Pirarubicin (PRB) which is known for its serious side effects was actively targeted to the breast cancer cells by uploading it to the biocompatible and biodegradable Sterically Stabilized Micelles (SSMs) made of 1,2-Distearoyl-sn-glycero-3 phosphoethanolamine-N-methoxy-polyethylene glycol 2000 (DSPE-PEG(2000)) to enhance efficacy and reduce toxicity. Vasoactive intestinal peptide (VIP), the receptors of which are overexpressed on the breast cancer cells, was grafted on the surface of the micelles. To the best of our knowledge this is the first report on active targeting of PRB to tumor site. For this purpose, PRB loaded VIP grafted SSMs (PRB-SSM-VIP) were synthesized and characterized. The in vitro efficiency of PRB-SSM-VIP along with SSM and free PRB was investigated on the MCF-7 breast cancer cells and the in vivo effects were studied on the 4T1 breast cancer bearing nude mice. Solubilizing 300 mu g of PRB using 2.81 mg of DSPE-PEG(2000) resulted in obtaining monodispersed particles of 12.16 +/- 2.7 nm with slow drug release profile. Incorporation of PRB within the hydrophobic DSPE core of SSM was confirmed using differential scanning calorimetry (DSC) and the spherical shape of the synthesized particles was demonstrated using atomic force microscope (AFM). Both in vitro and in vivo studies showed significantly higher activity of PRB-SSM-VIP compared to free PRB. In vivo imaging showed successful accumulation of PRB-SSM-VIP at the tumor site and 98.8% tumor eradication was obtained with no signs of side effects. Current study suggests that SSM-VIP could be used as new drug delivery system for targeting PRB to the breast cancer cells.
Keywords: Nanomedicine; Sterically stabilized micelle; Pirarubicin; VIP; Targeted cancer therapy; IN-VITRO; PHOSPHOLIPID MICELLES; DRUG-DELIVERY; VIVO; INTERNALIZATION; DERIVATIVES; FORMULATION; RECEPTORS; Pharmacology & Pharmacy